An overview of the contribution of the textiles sector to climate change - Leal Filho, Walter; Perry, Patsy; Heim, Hilde; Dinis, Maria Alzira Pimenta; Moda, Haruna; Ebhuoma, Eromose; Paço, Arminda (Frontiers in Environmental Science, 2022)
The textile industry is responsible for a significant amount of global CO2 emissions, exceeding those from several other sectors such as international aviation and shipping. This mini review outlines the reasons for the textile industry’s contribution to climate change along with an overview of current trends and finally outlines several measures to reduce its carbon footprint.